2022
DOI: 10.1177/14782103221113166
|View full text |Cite
|
Sign up to set email alerts
|

K-12 teachers conducting remote teaching in Thailand during the pandemic: The strategies, challenges and future directions

Abstract: This paper reports on a case study that examined the challenges faced and strategies adopted by Thai teachers when remote teaching during the COVID-19 pandemic. It further provides a comprehensive strategy for addressing the ongoing global pandemic in terms of education. We used a mixed methods design to collect both quantitative and qualitative data from K-12 Thai teachers ( N = 235) and performed 42 semi-structured interviews. The results indicated that most Thai teachers have the necessary knowledge to desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“… 8 , 9 Not only China but also Japan, the Philippines, and Thailand initially struggled to implement online learning for K-12 students. 10 , 11 There is a negative effect of school closures on academic performance among younger students during the COVID-19 pandemic. 12 Many educators and parents worry about K-12 students returning to school with lower academic performance when emergencies end.…”
Section: Introductionmentioning
confidence: 99%
“… 8 , 9 Not only China but also Japan, the Philippines, and Thailand initially struggled to implement online learning for K-12 students. 10 , 11 There is a negative effect of school closures on academic performance among younger students during the COVID-19 pandemic. 12 Many educators and parents worry about K-12 students returning to school with lower academic performance when emergencies end.…”
Section: Introductionmentioning
confidence: 99%
“…The results of studies conducted on the basis of Thai educational institutions showed that most teachers have the necessary knowledge to develop educational content for online learning. However, the formation of its communication elements requires them to develop administrative and leadership skills (Wetcho et al, 2022).…”
Section: Introductionmentioning
confidence: 99%